P203 HIV-testing African Service Users within a Newly Integrated Sexual Health Service - Our Experience. (30th June 2016) - Bulman, Joanna; Goode, Deborah; Evans, Amy
Abstract : Background/introduction: HIV testing is recommended for all sexual health clinic attendees, and in generic health services for high risk groups including BME communities, especially in areas of high HIV prevalence such as Leeds (2.51/1000). Aim(s)/objectives: In July 2015 an integrated contraception and STI service, Leeds Sexual Health, began following commissioning by Leeds local Authority wherein the routine offer of HIV testing was extended to all attending service sites across the city, 4 out of 5 of which had previously seen patients for contraception and sexual health (CASH) services only. Methods: We prospectively examined data in those of African ethnicity regarding offer and uptake of HIV testing in these new settings. Results: Interim data indicates a much higher number of African patients accessing the integrated service but with a lower overall uptake of HIV testing, a significant disparity in HIV testing uptake between men and women, with significant numbers of patients choosing not to disclose their known HIV status at a community setting where they are accustomed to only sharing contraception information. Discussion/conclusion: Staff used to achieving HIV testing rates of over 80% in a GUM clinic setting have found patients reluctant to test when they have come expecting the previous service. We are therefore trying to assess genuine missed opportunities for testing and considering reframing HIV testing as a positive and routine intervention e.g. along with postpartum contraception, when trying to embed HIV testing as part of a standard, integrated sexual health care offer.